Development of the portable posture training device - Yang, W. C.; Huang, W. H.; Chang, C. H.; Chung, K. C. (ISB Congress, 2005)
The aim of this study was to develop a portable posture training system by applying an audio-feedback signal to promote the active correction of the abnormal posture from subject`s muscle force [3] and to prevent continue deteriorated. This system could be used to detect a pre-set angle limitation of a joint and remind the patient adjusting to a suitable posture by audio warning when this angle limitation is violated.